PUBLIC RELATIONS STRATEGY IN ISSUE MANAGEMENT CUSTOMER SERVICE AT iBOX INDONESIA OUTLETS - Saraswati, Nyoman Aubinia; Juliadi, Rismi (Jurnal Komunikasi dan Bisnis, 2023)
Issue emerged at iBox Indonesia in 2020 after a video from content creator @julio.ioio on TikTok became viral. The issue regarding bad service that Julio experienced since he was putting on flip-flops while visiting the retailer. This incident feared to affect the reputation of PT Erajaya Swasembada, Tbk. as the holding company of iBox. This research aims to identify the public relations strategy of PT Erajaya Swasembada, Tbk in issue management of bad consumer service by iBox Indonesia employees. This research uses the qualitative descriptive with case study method. Data were obtained from the structured interviews with two participants and two informants. The results showed that PT Erajaya Swasembada, Tbk implemented management issue strategy started with media monitoring, Forum Group Discussion (FGD), pooling of opinion. The company analyzes the right public relations strategy and responds to issues through adaptive change strategy. The issue of handling the programs is divided into service and marketing communication program, however the evaluation could not be done systematically because Corporate Communication did not involve and did not involve much external parties either. PT Erajaya Swasembada, Tbk demonstrated a management issue program focused on the service quality provided for consumers. The company is able to maintain public trust and shows that they are serious in dealing with the issues for convenience and customers satisfaction to keep high reputation.